Hot runner technology - Unger, P. (Hanser, 2006)
Quality and profitability of injection molding operations can be considerably influenced by the hot runner system. The many variations and design principles of hot runners are material-dependent and therefore not universally applicable. Knowing about and recognizing these limitations will make or brake a molder's success. This book provides a comprehensive overview of the state-of-the-art in hot runner technology, advantageous design principles, and applications. The user will find the necessary basics as well as many proven designs and application examples.